Evaluation of indirect methods for determination of erodibility of Brazilian latosols (Oxisols) - Silva, Marx Leandro Naves; Curi, Nilton; Lima, José Maria de; Ferreira, Mozart Martins (Pesquisa Agropecuaria Brasileira, 2000)
There are three ways for determining the soil erodibility (K-factor). The first one includes the K-factor determination at field conditions, under natural rainfall, which is expensive and time consuming. The second method is similar to the first one, but it is based upon the quantification of K-factor as a function of soil losses and the erosivity factor, under simulated rainfall. The third method is based upon multiple regressions which include as independent variables soil attributes correlated with the K-factor obtained by the two former methods, considered as standards. The lack of basic data and the indefinition of the best method for the determination of the indirectly determined erodibility, which would allow to frame the soils into erosion resistance classes, constitute problems in the utilization of these indirect methods, particularly for the Brazilian Latosols (Oxisols). Therefore, this study aimed to determine the erodibility of these soils by indirect methods and the evaluation of the correlation between these methods and the direct ones. None of the tested methods allowed good estimation of erodibility for the set of Latosols of Brazil, being necessary the development of specific models for this group of soils.